Operation and Control of an Active Power Collector for Roadside Feeding Electric Road System - Saleh A. Ali; Volker Pickert; Mohammed A. Alharbi; Handong Li; Haris Patsios (IET Electrical Systems in Transportation)
The integration of electric vehicles (EVs) as an environmentally sustainable alternative to traditional fossil fuel cars faces a range of technological obstacles, including battery technology, charging infrastructure, and standardization. Dynamic conductive road charging (DCRC) of EVs at high speed has the potential to overcome the technical limitations of existing static charging methods. An intelligent motorway system for EVs called tracked electric vehicle (TEV) was proposed to incorporate the latest technologies of dynamic road charging, autonomous driving, and smart city data into transport infrastructure. This paper presents the operation and control of an active bipolar power collection unit (PCU) for the TEV system. The PCU is seamlessly integrated within the wheel structure of an EV using the concept of a stationary-hub wheel, enabling conductive power transfer from roadside conduction rails while the vehicle is in motion. The PCU is equipped with various features designed to maintain the contact force (CF) with the conduction rails, effectively handle instances of wheel bouncing and vibrations, and ensure a consistently smooth dynamic power transfer. This paper presents the experimental validations of the active PCU controls, including the operation sequence of the PCU, CF control, and PCU interaction with wheel bouncing.